Proceedings of the 2015 Conference on Innovations in Theoretical Computer Science 2015
DOI: 10.1145/2688073.2688097
|View full text |Cite
|
Sign up to set email alerts
|

Homophily and the Glass Ceiling Effect in Social Networks

Abstract: The glass ceiling effect has been defined in a recent US Federal Commission report as "the unseen, yet unbreakable barrier that keeps minorities and women from rising to the upper rungs of the corporate ladder, regardless of their qualifications or achievements". It is well documented that many societies and organizations exhibit a glass ceiling. In this paper we formally define and study the glass ceiling effect in social networks and propose a natural mathematical model, called the biased preferential attach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 36 publications
0
70
1
Order By: Relevance
“…Women's under-represented in higher education institutions and universities across the globe, and especially in the most powerful or influential posts, is well established (Avin et al 2015;Bruckmüller et al 2014;Cook and Glass 2014;Howe-Walsh et al 2014;Machado-Taylor and Özkanli 2013;Montez et al 2003;Taylor-Abdulai et al 2014;Zeng 2011) developing countries like Pakistan, is no exemption (Saher, Ali, & Matloob 2014). Higher education institutes and universities are facing increasingly complex challenges in attracting and retaining women (Uche et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Women's under-represented in higher education institutions and universities across the globe, and especially in the most powerful or influential posts, is well established (Avin et al 2015;Bruckmüller et al 2014;Cook and Glass 2014;Howe-Walsh et al 2014;Machado-Taylor and Özkanli 2013;Montez et al 2003;Taylor-Abdulai et al 2014;Zeng 2011) developing countries like Pakistan, is no exemption (Saher, Ali, & Matloob 2014). Higher education institutes and universities are facing increasingly complex challenges in attracting and retaining women (Uche et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another is having resources females feel comfortable using as they deem necessary [18]. In an effort to relate these disparities, there is research to support the experiences of females in classroom [19,20] and corporate settings [21]. However, these do not prescribe solutions for online community-based resources.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Increasing representation of women and scientists from a more diverse set of nations among 588 eLife's editor may lead to more diverse pool of peer reviewers and reviewing editors and a more 589 equitable peer review process. Editors often invite peer reviewers from their own professional 590 networks, networks that likely reflect the characteristics of the editor [76][77][78]; this can lead to 591 editors, who tend to be men [14, [67][68][69][70][71][72][73][74] and from scientifically advanced countries [75] to invite 592 peer reviewers who are demographically similar to themselves [44,79,80], inadvertently 593 excluding certain groups from the gatekeeping process. Accordingly, we found that male 594…”
mentioning
confidence: 99%